Pattern of vitreo-retinal diseases at University of Gondar tertiary eye care and training center, North-West Ethiopia - Abebe, Dagmawi; Tsegaw, Asamere (PLOS ONE, 2022)
Objective Vitreoretinal diseases are common causes of ocular morbidities and blindness. Data on the spectrum of vitreoretinal diseases needs to be studied and known in order to establish appropriate vitreoretinal care setups. The aim of this study was to determine the patterns of vitreoretinal diseases among patients who visited the vitreoretina clinic of University of Gondar Tertiary Eye Care and Training Center, NW Ethiopia (UoG-TECTC). Methodology A hospital based cross sectional study was conducted from October/2017-September/2018. All patients who visited the vitreoretinal clinic for the first time during the study period were studied. Data were collected with standardized data extraction format entered into SPSS statistical package Version 20 and analyzed. Result A total of 739 new patients who visited the vitreoretinal clinic were included in the study. The mean age was 50.26 +/- 19 years. The age group between 21–60 years accounted for 59.7% of study patients. Male’s accounted for 63.1% and 58.7% of the participants were from urban areas. Bilateral disease was diagnosed in 504 (68.2%) of patients and 220 (29.7%) were bilaterally blind at presentation. Three hundred eighty nine (52.6%) of them had duration of illness six months and above. Diabetic Retinopathy (DR), Age Related Macular Degeneration (AMD) and Rhegmatoginous Retinal Detachment (RRD) were the top three retinal diseases accounting for 21.3%(196), 17.3% (128) and 12.4% (92) of diagnoses respectively. Systemic comorbidities were found in 44% (325) of the patients with diabetes mellitus, hypertension and hyperlipidemia being the commonest, occurring in 27.8%, 6.3% and 2.8% of study patients respectively. Cataract was the commonest ocular comorbidity seen in 33.5% of study participants. Conclusion Vitreoretinal diseases affected a significant number of patients presented to our center and most of the study patients presented late with significant vision loss and blindness. Males were affected more than females and the age group between 21–60 years accounted nearly two-third of study patients. This is the working age group suffering from vision loss from vitreoretinal diseases. DR, AMD and RRD were the commonest retinal pathologies accounting for nearly half of the vitreoretinal diseases and these conditions are treatable either surgically or medically. However, available facilities for the management of these diseases are not adequate at the center. Strengthening the vitreoretinal services of UoG-TECTC with relevant equipment is recommended.